The pragmatic face of the covert idealist: the role of Allen Dulles in US policy discussions on Latin America, 1953–61 - Sewell, Bevan (Taylor & Francis, 2011)
Assessments of the CIA’s role in Latin America during the 1950s have tended to focus predominantly on the twin case-studies of Guatemala and Cuba. Consequently, the Agency’s role – and, more broadly, that of its head Allen Dulles – has come to be seen as one obsessed with covert action and relatively unimportant in terms of policy discussions. Dulles, in fact, has been portrayed as an unwilling and disinterested participant in policy discussions. The present article will challenge those assertions by suggesting that, by examining Dulles’s role in the Eisenhower administration’s discussions on Latin America, a different picture emerges – one that paints Dulles as an active and rational participant, and which raises important questions for our understanding of the CIA’s role during the Eisenhower era.